The maximum principle of pontryagin in control of two-legged robot based on human walking system - Żur, Krzysztof Kamil (Zielona Góra: Uniwersytet Zielonogórski)
In the paper a hypothesis about state equations of human gait is presented. Instantaneous normalized power developed by human muscles at particular joints of a leg is a control vector in state equations of the human walking system. The maximum principle of Pontryagin in analysis of dynamic human knee joint was presented. The discrete Hamilton function of a knee joint is similar to a discrete square function of normalized power developed by muscles at the knee joint. The results satisfy optimal conditions and could be applied in control of exoskeleton and DAR type robot.
Keywords: state equations; maximum principle; optimal conditions; discrete Hamilton function